Faith in the Workplace - Hanes, Pavel (The expository times, 2018)
In the following article an unbalanced theology of work is recognized as potentially jeopardizing a correct perception of our identity as workers and leading to problems in personal relationships in the workplace specifically. Against a background of philosophical and some popular contemporary views of work, the author points out the dimensions of work highlighted in the Bible. The article also shows how the biblical concept of work can become a caricature if one text is overemphasized at the expense of other balancing passages.